Pengaruh Model Pembelajaran Problem solving Berbantuan Canva Terhadap Kemampuan Pemecahan Masalah Siswa SD Negeri Ungaran 01 - Mekarsariningtyas, Dwi Puji; Rizqi, Hesti Yunitiara (Universitas PGRI Semarang, 2024)
Problem solving abilities in learning are based on the fact that some students have not completed problem solving questions, especially those related to daily life and what they have learned. Data analysis in this research is normality test, homogeneity test, hypothesis test in the form of regression test. The results of the research show that (1) There is an average difference in the application of the problem solving learning model assisted by Canva on the problem solving abilities of class III students at SD Negeri Ungaran 01, this is proven by the validator's assessment regarding the development of learning syllabus with an average of 3. 73, RPP with an average of 3.90, LKPD with an average of 3.5, and media with an average of 4.0. (2) There is an influence of the problem solving learning model assisted by Canva on the problem solving abilities of class III students at SD N Ungaran 01, as evidenced by the pre-test, post-test and activity scores showing a sig value of 0.000 0.05. The conclusion of this research is that the problem solving learning model assisted by Canva media on students' problem solving abilities is effective and very influential.